The Legal Status of Lineage and Inheritance Rights of Children Conceived After the Father’s Death (Posthumous Conception) in Islamic Jurisprudence - Aiman, Lajuba; Mahadewi, Kadek Julia (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
The advancement of assisted reproductive technology (ART) has raised new challenges in Islamic jurisprudence, particularly concerning lineage (nasab) and inheritance rights. One of the most complex bioethical and legal issues is posthumous conception, where a child is conceived after the father death using stored sperm or embryos. Classical Islamic law recognizes lineage only within a valid marriage (al firasy), which terminates upon the husband death, thus, posthumous conception questions the legitimacy of paternal lineage and inheritance. This study analyzes the legal position of such children under Islamic jurisprudence using a normative comparative method. It examines primary Islamic legal sources the Quran, Hadith, classical juristic opinions, and contemporary fatwas from institutions such as the OIC Fiqh Academy and Dar al Ifta al Misriyyah through the lens of maqasid al syariah. The findings confirm that posthumously conceived children cannot be attributed paternally because the marital bond has legally ended. Consequently, they are not entitled to inheritance under faraidh since they were not alive at the father death. Nevertheless, based on principles of justice (adl) and protection of lineage and wealth (hifz al nasl wa al mal), such children deserve moral and financial protection through non-inheritance mechanisms such as hibah or wasiat wajibah. The study concludes that Islamic law must adapt to biomedical developments while maintaining its core principles of lineage clarity, social justice, and compassion. This reinterpretation within the framework of maqasid al syariah ensures that Islamic family law remains just, humane, and responsive to modern ethical challenges